A Portrait of Teaching Writing in Online Classroom - Virga Putra Darma; Kunah Kunah; Siti Lina Nurlina; Salsa Ayu Denistiani (Departement of Mathematics Education, 2023)
Nowadays, online classrooms are growing in popularity. Especially given the Covid-19 outbreak in Indonesia, which has forced online learning. This study aims to investigate online learning in EFL learners’ writing classrooms. This study uses a qualitative method and a descriptive qualitative research design to examine in detail how teachers teach EFL learners in online writing. Researchers collected data through the technique of nonparticipant observation, and the researcher